Matrix representations of the national accounts’ transaction values - Santos, Susana (2021)
The values of economic flows measured by the national accounts, associated to transactions of goods, services, and assets, as well as transfers, represent interactions between institutional units, to whom legal responsibility for their actions and the fulfilment of specific economic functions is recognized. These flows are defined by the underlying system - System of National Accounts (SNA) as transactions. When represented in the matrix form, depending on the classification and organization of the institutional units, in the origin and the destination of the corresponding flows, the “from-whom-towhom” transactions can be measured and modelled, benefiting from the underlying network of linkages. By adopting the nomenclatures and rules of the current version of the above-mentioned system (SNA 2008), this study uses a top-down methodology to introduce two matrix representations of the national accounts’ transaction values. In these representations, the transactions are the same and the difference is in the form of classification and organization of the institutional units, in the origin and the destination of the corresponding flows, that is in the way how the rows and the columns of the matrices are represented. In one of these forms, the so-called National Accounting Matrix (NAM), the mentioned institutional units are only organized by institutional sectors, following the sequence of accounts defined by the SNA. In the other form, the so-called Social Accounting Matrix (SAM), only a part is organized in the same way as the previous, being given a different emphasis to the process of production in which these units are involved, namely, to the factors of production, activities (or industries) and products (or goods and services). The correspondence and the differences between both are identified and a SAM-based approach is developed. Thus, inspired in the Transaction Value (TV) Approach presented in Drud et al. 1986, empirical and theoretical descriptions of the economic activity of a country, allowed by numerical and algebraic versions of the SAM, are adopted to approach the multiplier effects and the corresponding economic adjustments of fiscal policy measures associated to the production of real estate activities. An application to Portugal follows the various aspects of the description.